Scrap : a novel - Henkel, Calla, 1988- (The Overlook Press, an imprint of ABRAMS, 2024)
Recently dumped and stuck with the mortgage, artist Esther Ray wants to burn the world, but instead, she reluctantly accepts a scrapbooking job from the deliriously wealthy Naomi Duncan. The scrapbooks, a secret birthday gift for Naomi's husband Bryce, trace the Duncan's twenty-five-year marriage. The conditions: Esther must include every piece of paper she's been sent, must sign an NDA, and must only contact Naomi using the burner phone provided. Otherwise she'll spoil the surprise. As Esther binges true-crime podcasts and works through the near-two hundred-boxes of Duncan detritus, she finds herself infatuated with the gilded family - until, mid-project, Naomi dies suspiciously. When Esther becomes convinced the husband killed her, she uses the scrapbooks' trove of information to insert herself into the Duncan's' lives to prove it. But the more Esther investigates, the further she is dragged back to the scorched earth of her past and the famous artist who paid her to disappear. Laced with pitch-black humour and conspiratorial unease, Scrap is a razor-sharp examination of wealth and power, art and truth, of the line between justice and revenge - and who gets to cross it.